The relationship between bladder wall thickness and lower urinary tract symptoms: Does bladder wall thickness change after alpha-blocker therapy with alfuzosin? - Karakose, Ayhan; Aydogdu, Ozgu; Atesci, Yusuf Ziya (Canadian Urological Association Journal, 2014)
Introduction: We evaluate the association between lower urinary tract symptoms (LUTS) and bladder wall thickness (BWT) and investigate whether alfuzosin might improve BWT. Methods: We retrospectively reviewed the data of 164 patients with LUTS. Patients were divided into 2 groups according to BWT(Group 1: BWT ≤5 mm, n = 69; Group 2: BWT >5 mm, n = 95). Age, international prostate symptom score (IPSS), maximum and average urinary flow rates (Qmax and Qave), quality of life (QoL), postvoid residual (PVR) urine volume, prostate volume and prostate-specific antigen (PSA) were compared between the 2 groups. In total, 102 patients underwent transurethral resection of the prostate (TURP) and 62 patients were treated with alfuzosin. We compared BWT, Qmax, Qave, IPSS, QoL, PVR and PSA before and at the sixth month of alfuzosin therapy. A p value of <0.05 was considered statistically significant. Results: The mean BWT of Group 1 was 3.72 ± 0.56 mm and Group 2 was 6.43 ± 1.13 mm. There was a significant difference between the 2 groups in terms of mean Qmax and PVR. There was no statistical difference between the groups in terms of Qave, IPSS, QoL, prostate volume and PSA. There was significant difference between BWT before (6.8 ± 2.1) and after (4.6 ± 1.3) treatment with alfuzosin in 62 patients (p = 0.02). There was a significant difference between pre- and post-treatment values of mean Qmax, Qave, IPSS, QoL score, and PVR with alfuzosin. Conclusion: BWT is a non-invasive and effective test to evaluate patients with lower urinary tract obstruction and may be used for showing the effectiveness of alpha-blocker therapy in patients with LUTS.